Analisis Pencapaian Dimensi Pengetahuan Siswa SMA pada Materi Asam Basa Ditinjau dari Gaya Belajar - Eni, Baiq Nopita Handra; Idrus, Syarifa Wahidah Al Idrus; Supriadi, Supriadi; Junaidi, Eka Junaidi (Chemistry Education Practice, 2024)
This research is a quantitative descriptive study with the aim of analyzing the achievement of the knowledge dimensions of class XI MIPA students at SMA Negeri 1 Terara on acid-base material in terms of learning styles. This study involved 102 students as a sample with a sampling technique using simple random sampling. Collecting data using a learning style questionnaire instrument and test questions for the achievement of students' knowledge dimensions. The results of the validity of the learning style questionnaire instrument and the test questions for the achievement of student knowledge dimensions obtained from three validators, namely 0.81 and 0.78, respectively, are valid and can be used to measure the tendency of learning styles and the level of achievement of students' knowledge dimensions but need revision. The results of the study for the learning style questionnaire showed that of 102 students of class XI MIPA at SMA Negeri 1 Terara there were 47 students (46.08%) who had a visual learning style tendency, 29 students (28.43%) who had an auditory learning style tendency, and there are 26 students (25.49%) who have a tendency to auditory learning style. This shows that the dominant learning style owned by students of class XI MIPA at SMA Negeri 1 Terara is a visual learning style. The achievement of students' knowledge dimensions based on learning styles obtained an average test score of 43.42 for students with visual learning styles, 40.45 for students with auditory learning styles, and 43.33 for students with kinesthetic learning styles. This shows that the achievement of the knowledge dimensions of class XI MIPA students at SMA Negeri 1 Terara belongs to the low category.